Do mergers and acquisitions leads to a higher technical and scale efficiency? a counter evidence from Malaysia - Sufian, Fadzlan; Habibullah, Muzafar Shah (Academic Journals, 2009)
The present paper examines the impact of mergers and acquisitions on the technical efficiency of the Malaysian banking sector. The analysis consists of two stages. Firstly, by using the Data Envelopment Analysis (DEA) approach, we calculate the technical, pure technical, and scale efficiency of individual banks during the period 1997-2003. Secondly, we examine changes in the efficiency of the Malaysian banking sector during the pre and post merger periods by using a series of parametric and non-parametric univariate tests. Although the merger programme was unpopular, perceived by the market as impractical, and controversial, the empirical findings from this study suggest that the merger programme among the Malaysian domestic commercial banks was driven by economic reasons.